Investigation of Electrophysiological Features During Mental Workload Paradigm - (:unkn) unknown (IEEE, 2016)
In the last few decades, the relationship between the mental workload and electrophysiological measurements are being studied. The aim of this study is to measure the electrophysiological responses of the autonomic and central nervous system to the increased mental workload. In this concept, backwards counting paradigm is used to increase the mental workload while the brain electrical activity (EEG), hearth rate variability (HRV) and electrodermal activity has been measured synchronously. During the increased mental workload, EEG alpha band suppression and increased EDA were observed. On the other hand, hearth rate variability has not been changed with respect to paradigm.
Keywords: mental workload; alpha suppression; electrophysiology; BRAIN; TASK